Optimalisasi kondisi aktivasi arang bonggol jagung sebagai desikan menggunakan metode Taguchi - Tri Hadi Jatmiko; Donovan Rendi Suherman; Rinaldi Medali Rachman; Anggita Sari Praharasti; Dwi Joko Prasetyo (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Preserving food can be achieved through several methods, one of which is drying. Dried foods are easier to store and distribute. Environmental factors such as temperature and humidity play a crucial role in food preservation and must be controlled to increase its shelf life. A desiccant can be used to regulate humidity levels. Activated carbon is a material that can be used as a desiccant, which can be produced from biomass such as corn cobs. This study focuses on optimizing the conditions for using corncob charcoal as a desiccant by using a Taguchi orthogonal array. The optimization process involves determining the optimal KOH concentration, immersion time, and the ratio of charcoal to KOH volume. Results showed that KOH concentration was the most significant factor in activating carbon from corn cobs, followed by the ratio and immersion time. The optimal conditions for activating carbon from corn cobs as a desiccant were found to be a KOH concentration of 2%, a ratio of 10 g charcoal to 150 mL KOH, and an immersion time of 2 hours, resulting in a water vapor adsorption capacity of 0.3949 g/g